2015
DOI: 10.1007/s11695-015-1824-2
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Rates and Weight Loss After Roux-en-Y Gastric Bypass, Sleeve Gastrectomy, and Adjustable Gastric Banding in Patients Older Than 60 Years old: Which Procedure to Choose?

Abstract: LSG showed the lowest readmission and reoperation rate, and RYGB patients had the highest mortality rate. Weight loss and comorbidity resolution were effectively achieved in RYGB and LSG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…Studies comparing types of surgery reported that RYGB was associated with greater or equal weight loss compared with sleeve gastrectomy, and both RYGB and sleeve gastrectomy were associated with more weight loss than LAGB . Most studies reported rates of resolution of type 2 diabetes, which ranged widely from 22% to 100%, apart from the study by Moon and colleagues which reported remission of diabetes a mean of 24 months post‐operatively in only 10% of patients after LAGB, 19% after RYGB, and 34% after SG . Studies generally did not find a significant difference in diabetes resolution rates in the older compared with younger group, although a higher rate of diabetes remission was reported in participants under the age of 40, compared with the ≥60 year old group in one study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies comparing types of surgery reported that RYGB was associated with greater or equal weight loss compared with sleeve gastrectomy, and both RYGB and sleeve gastrectomy were associated with more weight loss than LAGB . Most studies reported rates of resolution of type 2 diabetes, which ranged widely from 22% to 100%, apart from the study by Moon and colleagues which reported remission of diabetes a mean of 24 months post‐operatively in only 10% of patients after LAGB, 19% after RYGB, and 34% after SG . Studies generally did not find a significant difference in diabetes resolution rates in the older compared with younger group, although a higher rate of diabetes remission was reported in participants under the age of 40, compared with the ≥60 year old group in one study .…”
Section: Resultsmentioning
confidence: 99%
“…No studies found significantly greater weight loss in the older compared with younger group. Studies in which percentage total weight loss (%TWL) was reported in older people found loss of 17% to 38% after 1 to 6 years following gastric bypass and sleeve gastrectomy, and loss of 14% to 20% after adjustable gastric banding . For studies in which weight outcome was reported as percentage excess weight loss (%EWL), older persons undergoing RYGB or LSG lost 46% to 77% excess weight at 12 to 21 months, and 43% to 72% 2 to 6 years post‐operatively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite its effectiveness, it is estimated that less than 1-2% of obese patients potentially eligible for bariatric surgery eventually undergo these procedures (2). This is primarily due to the high cost associated with this surgery, its associated morbidity (15-20% of major complications) and potential mortality (very limited in the last few years), and persistent social "fear" (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is controversy on the implementation of bariatric surgery across the age range . In fact, few data exist examining the risks and/or benefits of bariatric surgery in older adults . Interestingly, some but not all studies report that older people have smaller weight loss and comorbidity resolution following surgery.…”
Section: Introductionmentioning
confidence: 99%